Are there differences in jump height and muscle activation pattern across sand and rigid surface specific athletes? - Brodatzki, Y.; Wirtz, S.; Szwajca, S.; Büsch, D.; Zentgraf, K.; Eils, E. (Book of Abstracts of the 24th Annual Congress of the European College of Sport Science - 3rd - 6th July 2019, Prague - Czech Republic, 2019)
• Beach handball has not been investigated in laboratory settings yet • Sand as preventive surface, e.g. recovery and rehabilitation (Binnie et al., 2013; Balasas et al., 2018) • Importance for research on uneven or unstable surfaces has increased (Arampatzis et al., 2001; Lesinski et al., 2017) • Significant main effects of "surface" were observed for tibialis anterior (TA) and gastrocnemius medialis (GM) activity during the preactivation phase (Lesinski et al., 2017)